Corrosion morphology of prestressing steel strands in naturally corroded PC beams. (16th August 2021) - Vecchi, Francesca; Franceschini, Lorenzo; Tondolo, Francesco; Belletti, Beatrice; Sánchez Montero, Javier; Minetola, Paolo
Highlights: Experimental study on different types of pits morphologies. Comparison of pit morphologies in terms of depth, transversal and longitudinal width. Useful correlation between maximum pit depth and mass loss for any corrosion rates. Probability distribution of maximum pit depth. The pitting factor is evaluated for natural corroded strands. Abstract: The geometric morphology of pits induced by corrosion has been investigated. To this aim, twenty-four seven-wire strands coming from 10 years old naturally corroded prestressed concrete beams have been analysed. The cross-sections of corroded strands were measured and examined in detail. The morphology of corrosion pits has been recorded by using a structured light 3D scanner and classified in terms of maximum pit depth, longitudinal dimension, and transversal width. Then, a new method for the approximate evaluation of the average pit depth of prestressing strands has been proposed. Finally, the pitting factor of the corroded samples has been calculated.